Development of in-pipe inspection robot: A review - Ismail I.N.; Anuar A.; Sahari K.S.M.; Baharuddin M.Z.; Fairuz M.; Jalal A.; Saad J.M. (2023)
This paper reviewed several previous papers on work that have been done on the development of in-pipe inspection robot for the last 20 years. By sorting the types of the inspection robots they can be divided into several groups according to their locomotion. Each prototype has its own advantages and disadvantages depending on its design requirements and purpose of inspection. The prototypes have been tested in several experiments in order to verify its functionality and efficiency of inspection task. Some of the researchers ran simulations to validate the kinematic and modeling the mechanism of their own prototype. Developing in-pipe inspection robot can overcome the issues of human factor in labour intensive or dangerous work and also to act in inaccessible environment during repair and maintaining inside the pipeline. 2012 IEEE.